Asymptotic expansions associated with the jackknife functional. I - Ivanov, O. V.; Bardadym Т. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We obtain an asymptotic expansion of the functional of the jackknife method, which is used for the estimation of the variance of observational errors in a nonlinear regression model.